STUDIES ON THE CHARACTERIZATION AND DISTRIBUTION OF FATTY ACIDS AND MINORCOMPONENTS OF HIGH-ERUCIC ACID MUSTARD OIL AND LOW-ERUCIC ACID RAPESEED OIL - Alim, Md. Abdul; Alim, Md. Abdul; Iqbal, Zafar; Dutta, Paresh C. (Emirates Journal of Food and Agriculture, 2012)
The aim of this work was to compare the positional fatty acid composition, sterols, tocopherols and oxidative stability of mustard oil (MO) and rapeseed oil (RSO). The MO contained higher levels of erucic acid (42.8%) and linolenic acid (18.2%), compared with RSO (0.4 and 8.6%) whereas the RSO contained higher levels of oleic acid (62.2%) and linoleic acid (19.5%), than that of MO (17.4 and 15.8%). The changing fatty acid compositions at different position led to different physical properties. The ?-6/?-3 ratio of MO and RSO were 0.87 and 2.27, respectively. The balance of ?-6/?-3 ratio is also an important determinant in decreasing the risk for coronary heart disease. MO contained higher amount of total tocopherols (38.32 mg/100g) but lower amount of total sterols (606.32 mg/100g) than that of RSO (631.98 mg/100g and 25.57 mg/100g). The oxidative stability determined by Rancimat test of MO (PF, 1.57) was higher compared with RSO (PF, 1.0).